How can spirituality make meaning and give health benefits for Sami elders? - Nymo, Randi Inger Johanne (2019)
Presentation at the NAISA 2019 annual meeting at University of Waikato, Hamilton, New Zealand, 26.06. - 29.06.19, arranged by Native American and Indigenous Studies Association (NAISA). https://www.naisa.org/.